ANALISIS KEBIJAKAN POLITIK HUKUM PEMERINTAH KOTA CILEGON ATAS PENINGKATAN PEMBANGUNAN EKONOMI TAHUN 2010-2015 - fatoni, malik (CosmoGov, 2018)
ABSTRACT The research aims to find out how far the effectiveness of some of the making and stipulation of regulations and legislation support efforts to improve economic development, as happened in cilegon city. efforts to obtain the achievements and progress for the improvement of economic development need to be done policy analysis on matters relating to political and legal policy for then conducted a review of documents, observation and interview. thereby facilitating an analytical, constructive, explorative and documentative study. this is often called the data triangulation method. namely a method that combines various methods of data collection. The study was carried out in Cilegon city, divided into 4 stages: 1). preparation stage: preparation of proposals. 2). implementation stage: data collection and processing, 3). Reporting stage: preparation of reports and accountability. 4). stages of publication: dissemination in local and / or national seminars and publications in accredited scientific journals. In this research the methodology used is Qualitiative with Grounded Theory Approach. data collection techniques is by data triangulation method. this is often called a method that combines various methods of data collection, such as observation, interviews and documentation. from this research is expected to increase the productivity of policies and efficiency of planning programs in the field of politics and law formulated by the regional government of Cilegon city can increase economic development and peoples welfare. The results achieved from this research is the policy of political law conducted by the City Government Cilegon can push for the increase of regional economic development, it can be seen from the legislation product that legitimately by the Parliament of Cilegon City in quality and quantity has been so good that the product can well executed by the executive and provide juridical strength for the City Government of Cilegon in the improvement of economic development, as seen from the indicators of improvement of economic development itself. The political policy of law that is processed and synergized between government institutions in Kota Cilegon, indicates the strong and strong commitment of these institutions to encourage and promote economic development on an ongoing and measurable basis. Keywords: Political Law, Regional Government, Economic Developmen